Psychosocial burden and healthcare disillusionment in recurrent UTI: a large-scale international survey of patient perspectives - Maxwell, Kayleigh; Roberts, Lindsey; Kramer, Melissa; Price, Jessica; Newlands, Abigail; Finlay, Katherine A. (Frontiers in Urology, 2023)
Objectives Recurrent UTI (rUTI) is a debilitating health condition that is associated with persistent mental, physical, and social burdens. People living with rUTI face inconsistencies in diagnostic testing and fragmented treatment pathways alongside their symptoms, which are likely to add considerably to their illness-related burdens. This study aimed to characterize the factors negatively impacting this population using the qualitative perspectives of people living with the condition. Methods Qualitative data were collected via free-text responses using an online survey hosted by an rUTI patient advocacy website. Female participants with self-reported rUTI (n = 1,983) described the factors that were most salient to their experience of living with the condition. Data were analyzed using a coding reliability approach to thematic analysis. Results Two overarching themes were identified: (1) the patient burden of rUTI, which describes the multifaceted biopsychosocial impact of the illness, and (2) healthcare disillusionment, which describes patient dissatisfaction with healthcare received, both in terms of the treatments offered and communication with healthcare professionals. The patient burden of rUTI encompassed four subordinate themes: facing ongoing uncertainty; symptom salience; sex is not simple anymore; and perceived UTI stigma. Healthcare disillusionment included three subordinate themes: discomfort with frequent antibiotic use; fragmented treatment pathways; and devalued patient perspectives. Conclusions The findings demonstrated that ambiguity in the diagnosis of rUTI and inconsistencies in the subsequent treatment pathway are exacerbated by poor patient–clinician communication. The extent of the female-specific burden of rUTI symptoms confirmed the harmful effects of illness-related stigma. This novel qualitative reporting of rUTI symptom burden and life impact highlights the urgent need for increased patient-centered care for those living with rUTI. More effective rUTI management could have a major impact on treatment outcomes and patient-reported psychosocial wellbeing.